Tourism and the Accumulation of Capital: A Perspective on the Reserve of the Biosfera Sian Ka’an - Alejandra Rojas Correa; Alejandro Palafox-Muñoz (Íconos)
In this research we analyze the way in which tourism has worked as a means to facilitate the accumulation of capital inside the Reserve of the Biosfera Sian Ka’an, Quintana Roo, Mexico. This article explores how, though the discourse of sustainability imposed by international organizations, the advancement of capital has been allowed in protected natural areas. The amplification of capital is made possible thanks to the policies of a capitalist system that have become strengthened by the current neoliberal project, where the States permits the dispossession of natural resources of indigenous peoples, yielding their control to private interests that aim to increase their capital through an economic activity, such as tourism. This process is studied drawing from a theoretical proposal of three dynamics of accumulation of capital in protected natural areas: penetration, subsumption, and enclosure.